UPAYA ORANGTUA DALAM MENINGKATKAN PRESTASI ANAK DI DESA PARIT RAJA KECAMATAN SEJANGKUNG PADA MASA PANDEMI COVID-19 TAHUN 2020 - Resky Nurul Fitri; Rusiadi Rusiadi; Rona Rona (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This research was conducted in response to the phenomenon of poor learning outcomes among children, which has prompted parents to seek ways to improve their children's academic performance. The objectives of this study were to describe the planning of parents' efforts to improve their children's achievements in Sekura Village, Kelumpang Hamlet, in 2019, and to describe the factors that supported and hindered parents' efforts to improve their children's achievements in Parit Raja Village, Sejangkung Subdistrict, during the COVID-19 pandemic in 2020. The results of the study can be summarised as follows: 1) Parents' efforts to improve their children's academic performance in Parit Raja Village, Sejangkung District, in 2019 included various child-centred approaches, such as showing affection to their children and giving them rewards, which had a positive impact on the children and motivated them to study at home. Parents also collaborated with teachers to improve their children's learning and set a good example for their children. 2) Supporting and inhibiting factors in parents' efforts to improve their children's achievement in Parit Raja Village, Sejangkung District, during the COVID-19 pandemic in 2020: Supporting factors include: appropriate use of technology, good social interactions in the community and a harmonious family, maintaining children's health and following health protocols, cooperation between teachers and parents to improve children's learning achievement, high interest and motivation to learn, a good family environment at home, and a good community environment. The inhibiting factors are: low parental educational background, lack of cooperation between parents and teachers in improving children's learning achievements, parents who do not pay attention to their children's education, including: being indifferent to their children's learning process, never paying attention to their children's interests and needs in learning, not managing their children's learning time, not providing or completing learning equipment, not wanting to know about their children's learning progress, and the difficulties faced by children in learning.